RADT-15. 18F-DOPA PET/CT SURVEILLANCE FOR GLIOBLASTOMA: A RADIOMIC MODEL FROM A PROSPECTIVE PHASE II CLINICAL TRIAL PREDICTING SURVIVAL IN IDH-WILDTYPE, MGMT-UNMETHYLATED PATIENTS. (14th November 2022) - Qian, Jing; Pafundi, Deanna; Breen, William; Brown, Paul; Hunt, Christopher; Jacobson, Mark; Johnson, Derek; Kaufmann, Timothy; Kemp, Bradley; Kizilbash, Sani; Lowe, Val; Ruff, Michael; et al.
Abstract: BACKGROUND: Interpretation of serial magnetic resonance imaging (MRI) for glioblastoma following radiation therapy (RT) is complicated by difficulty differentiating tumor from treatment-related changes, even using updated RANO criteria. The incorporation of novel imaging such as 3, 4-dihydroxy-6-[18F]-fluoro-L-phenylalanine ( 18F -DOPA) PET/CT to post-treatment serial imaging may improve prognostication and better facilitate future treatment decisions. METHODS: The secondary analysis of a recent phase II prospective clinical trial of 18 F-DOPA PET/CT-directed dose-escalated RT included patients with IDH-wildtype, MGMT-unmethylated glioblastoma who underwent post-treatment serial 18F-DOPA PET/CT surveillance. Quantitative features were extracted from pre-RT and post-RT serial PET/CT images, and robust prognostic features were selected using an in-house workflow. Both an automated machine learning (ML) algorithm and an interpretable ML algorithm were utilized to correlate surveillance PET image features with subsequent survival of greater than 12 months versus less than 12 months from the surveillance timepoint. Changes from pre-RT to post-RT PET/CT (delta model) were also assessed for association with post-RT survival and validated with a separate cohort. RESULTS: Thirty-five patients with IDH-wildtype, MGMT-unmethylated glioblastoma who had at least one available (range: 1-14) post-treatment 18 F-DOPA PET/CT were included. Twenty-four were used for model training, while 11 were used for validation. Ultimately, a five-feature post-RT model utilizing two shape, two texture, and one first-order radiomic feature was selected. For the delta model, five texture, two shape, and one first order radiomic feature were selected. The models show 90% accuracy in predicting survival < 12 months post-surveillance on the training set, and 68%-73% accuracy (AUC 0.64-0.73) for the validation cohort. Delta features were significantly associated with overall survival (p < 0.05). CONCLUSIONS: Post-RT serial 18 F-DOPA PET/CT imaging can help distinguish true tumor progression in patients with glioblastoma using a radiomics model. Tumor response evaluated for changes from pre-RT to post-RT 18F-DOPA PET/CT also predicted subsequent overall survival.